To what extent is capital expenditure in UK higher education meeting the pedagogical needs of staff and students?. Issue 4 (3rd July 2016) - Jones, Steven; Sutcliffe, Michael J.; Bragg, Joanna; Harris, Diane
ABSTRACT: Capital expenditure at United Kingdom (UK) universities is rapidly rising, with new buildings erected on the premise that national and international competitiveness must be maintained. We examine students' engagement with and conceptualisation of university estate, and explore broader questions about the extent to which building design can support, and indeed change, students' approaches to learning. Drawing on data collected from 10 staff members and over 200 students at a major UK institution, including detailed one-to-one interviews, we capture users' often complex interactions with their university environment. Our findings confirm that when asked what would most improve their learning experience, students do not rank building design highly; interactional factors, such as contact time with staff, are considered more valuable. Our conclusion is that returns on capital investment would be boosted if pedagogical needs were prioritised more highly in the design of university buildings, and pedagogical opportunities communicated more clearly to users upon completion.